THE PRINCIPLE OF SOCIAL JUSTICE AS THE LAW - Prastyo, Brian Amy (Jurnal IUS, 2013)
The term of âsocial justiceâ has mentioned explicitly in Pancasila. As the nation philosophical base, every Indonesian citizen may interpret the meaning of this term. Interpretation of every citizen may be various caused by each personal have their own way of thinking. This article offered a picture of how the âsocial justiceâ term could be interpret in 4 points of view, that are; Indonesianist, liberalist, Islamic and post modernist point of view. Furthermore this article will shows basic similarity among four ideas above concerning âsocial justiceâ so that we could see the harmony among them in interpreting âsocial justiceâ term. In the end will be described how âsocial justiceâ term embraced as a principle and normatively functioned. That is as a guidance to state rights and obligations which in certain situation could hold stronger power than a valid regulation. Keywords: Justice Theory, Legal Positivism, Pancasila, Social Justice, Basic Right.Abstrak: